Helping students in crisis - Quality Educational Media (Albuquerque : Quality Educational Media, Inc., 2001)
Presentation by Jane Bluestein, also author of Creating Emotionally Safe Schools
QEM numbers : Pt. 1, QEM-2131 ; Pt. 2, QEM-2132
Speaker, Jane Schools
VHS
Keywords: Classroom management -- Safety measures; Schools -- United States -- Safety measures; School environment -- United States -- Psychological aspects